2023
DOI: 10.1039/d2na00755j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sr and Ti substitutions on optical and photocatalytic properties of Bi1−xSrxFe1−xTixO3 nanomaterials

Abstract: The potential use of down-sized BFO-xSTO systems x ≤ 25% as highly efficient photoanodes for photocatalytic water splitting reaction is investigated. BFO-xSTO is prepared by solid-state method, and subsequently deposited...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Apart from these characteristics, the key property required in a photocatalyst material for efficient water splitting is the appropriate band alignment with water’s redox potentials. It was previously demonstrated that BFO presents a good alignment with the oxidation potential of water, suggesting an effective O 2 evolution reaction (OER) [ 76 ]. Nonetheless, lowering its conduction band minimum (E CB ) below the EH + /H 2 energy remains needed to enable an efficient H 2 evolution reaction (HER) ( Figure 1 c) [ 76 ].…”
Section: Bismuth Ferritementioning
confidence: 99%
See 2 more Smart Citations
“…Apart from these characteristics, the key property required in a photocatalyst material for efficient water splitting is the appropriate band alignment with water’s redox potentials. It was previously demonstrated that BFO presents a good alignment with the oxidation potential of water, suggesting an effective O 2 evolution reaction (OER) [ 76 ]. Nonetheless, lowering its conduction band minimum (E CB ) below the EH + /H 2 energy remains needed to enable an efficient H 2 evolution reaction (HER) ( Figure 1 c) [ 76 ].…”
Section: Bismuth Ferritementioning
confidence: 99%
“…It was previously demonstrated that BFO presents a good alignment with the oxidation potential of water, suggesting an effective O 2 evolution reaction (OER) [ 76 ]. Nonetheless, lowering its conduction band minimum (E CB ) below the EH + /H 2 energy remains needed to enable an efficient H 2 evolution reaction (HER) ( Figure 1 c) [ 76 ]. This requirement has driven numerous research efforts for enhancing BFO photocatalytic characteristics to achieve more efficient and substantial H 2 production.…”
Section: Bismuth Ferritementioning
confidence: 99%
See 1 more Smart Citation